P368 Safety issues of azathioprine in patients with inflammatory bowel disease: clinical experience from a referral center. (21st January 2022) - Fousekis, F; Kourtis, G; Saridi, M; Albani, E; Katsanos, K; Christodoulou, D
Abstract: Background: Despite the development new agents for inflammatory bowel disease (IBD) therapy, azathioprine (AZA) is widely used as both as monotherapy and as combination therapy for induction and maintenance of remission both Crohn's disease (CD) and ulcerative colitis (UC). Aim of this study is to investigate the long-term safety of AZA, to document the prevalence of adverse events of AZA in patients with IBD. Methods: In this retrospective study, we included, 222 patients with IBD, who were monitored at University hospital of Ioannina from, 2003 to, 2019. The diagnosis of IBD was made based on endoscopic and histologic findings after ileocolonoscopy with biopsies. Inclusion criteria of study were diagnosis of IBD and regular follow-up intervals at least every six month after start of AZA administration. Results: The average age of patients was, 46.9 years (Std. Dev., 17, 9) at start of AZA administration., 65.6% of IBD patients (146/222) had CD and, 34.4% had UC (76/222). The mean duration of AZA administration was, 51 months (range:, 0–135 months). The most frequent location of CD was ileocolonic (38.4%, 56/146), while the most patients with UC had left sided colitis (54%, 41/76). Furthermore, the main indication for AZA treatment was the maintenance of remission both in UC and CD. The most common dose of AZA was, 100mg/day (range:, 50-200mg). The most common adverse events were gastrointestinal symptoms (8.6%, 18/222), leucopenia (2.7%, 6/222), hepatotoxicity (5.4%, 12/222) and pancreatitis (1.8%, 4/222). Two patients were diagnosed with basal cell cancer. Infections were recorded in, 19 patients (8.6%) of whom, 6 needed hospitalization. Conclusion: According to this retrospective observational study, approximately one-third of IBD patients receiving AZA presented clinical significant adverse event during follow-up. Azathioprine withdrawal or dose reduction was needed in, 47 (21%) patients.